Distributed feedback lasers with distributed phase-shift structure - Chen, G.; Seshadri, S. R.; Cerrina, F. (Applied physics letters, 1992)
Distributed feedback (DFB) lasers with distributed phase-shift (DPS) structures are suggested for reducing the spatial hole burning in conventional phase-shifted DFB lasers. Solving the coupled-mode equations subject to suitable boundary conditions, we have determined the threshold gain condition of a symmetric distributed phase-shift distributed feedback (DPSDFB) laser as well as the internal photon intensity distribution. The results show that by distributing the phase shift to a greater extent, the spatial hole burning can be reduced significantly and a large threshold gain difference between lowest gain oscillation modes can be maintained over a large phase-shift range. Moreover, a properly designed DPSDFB laser does not pose extra requirements on its fabrication.